Lateness and Modernity in Medieval Architecture
1 online resource (504 pages)
Keywords: How have the concepts of “lateness” and “modernity” inflected the study of medieval and early modern architecture? This volume seeks to (re)situate monuments from the 14th—16th centuries that are indebted to medieval building practices and designs within the more established narratives of art and architectural history. Drawing on case studies from Cyprus to the Dominican Republic, the book explores historiographical, methodological, and theoretical concerns related to the study of medieval architecture, bringing to the fore the meanings and functions of the Gothic in specific contexts of use and display. The development of local styles relative to competing traditions, and instances of coexistence and hybridization, are considered in relation to workshop practices and design theory, the role of ornament, the circulation of people and knowledge, spatial experiences, as well as notions of old and new. Contributors are: Jakub Adamski, Flaminia Bardati, Costanza Beltrami, Robert Bork, Jana Gajdošová, Maile S. Hutterer, Jacqueline Jung, Alice Klima, Abby McGehee, Paul Niell, Michalis Olympios, Zachary Stewart, Alice Isabella Sullivan, Kyle G. Sweeney, and Marek Walczak.